Method for producing polyacetal copolymer
Patent Information
- Application Number
- JP2020162094
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-28
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2040-09-28
AI Technical Summary
【0014】 本発明によれば、優れた剛性、耐クリープ特性等を有し、熱安定性も兼備したポリアセタール共重合体と、その安定な製造方法を提供することができる。
Smart Images

Figure 0007641100000001 
Figure 0007641100000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyacetal copolymer and a method for producing the same. [Background technology]
[0002] Polyacetal resin has an excellent balance of mechanical properties, chemical resistance, sliding properties, etc., and is easy to process, so it is widely used as an engineering plastic, mainly in electrical and electronic parts, automobile parts, and various other machine parts. However, as the range of its use expands in recent years, there is a tendency for more advanced properties to be required. For example, when using polyacetal resin for thin-walled parts, etc., it is often required to maintain the inherent fluidity, moldability, thermal stability, and sliding properties of polyacetal resin, while also exhibiting rigidity, creep resistance, etc.
[0003] However, it is extremely difficult to satisfy the above required properties in a well-balanced manner. For example, a method of blending a fibrous or other filler into a polyacetal resin to improve rigidity may result in poor appearance of the molded product, reduced sliding properties, reduced fluidity, etc., and furthermore, depending on the filler blended, the thermal stability may be reduced. It is also known that the rigidity of a polyacetal copolymer can be improved by reducing the amount of comonomer to be copolymerized. However, the improvement in rigidity achieved by this method is not sufficient, and on the other hand, the reduced amount of comonomer reduces the thermal stability of the polymer, which in turn adversely affects the fluidity, moldability, etc.
[0004] In view of the above-mentioned circumstances, the present inventors have conducted studies focusing on improving the rigidity and creep properties by modifying the polymer skeleton of the polyacetal resin itself, and have proposed methods for improving the same (see Patent Documents 1 to 3). These methods can improve the rigidity, creep resistance, etc., while maintaining the excellent fluidity, moldability, sliding properties, etc., inherent to polyacetal resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2000-38429 A [Patent Document 2] JP 2000-95829 A [Patent Document 3] JP 2000-95830 A Summary of the Invention [Problem to be solved by the invention]
[0006] The polyacetal copolymers obtained by the above-mentioned methods are basically good in terms of thermal stability. However, further investigations have revealed that the operations during production, such as the polymerization step, the terminal stabilization step, or the melt-kneading step with a stabilizer or other compound, can be unstable, and the thermal stability of the copolymers obtained can be poor. Clarification of the causes and improvement of these problems have been important issues in commercializing polyacetal copolymers produced by these methods.
[0007] The present invention has been made in consideration of the above-mentioned problems in the conventional art, and an object of the present invention is to provide a polyacetal copolymer having excellent rigidity, creep resistance, etc., and also having thermal stability, and a stable method for producing the same. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems and have found that the chlorine content in an aliphatic glycidyl ether compound used for forming a branched / crosslinked structure in the polymer skeleton of a polyacetal copolymer is a key factor for solving the problems, and have also found a suitable range for the MFR (melt flow rate) of the polyacetal copolymer and a means for controlling the same, thereby completing the present invention.
[0009] One aspect of the present invention that solves the above problems is as follows. (1) 100 parts by mass of trioxane (A) and 0.05 to 10 parts by mass of a cyclic acetal compound (B) and 0.001 to 1 part by mass of an aliphatic glycidyl ether compound (C) having a chlorine content of 1 to 500 ppm by mass in the presence of a linear formal compound (D) as a molecular weight regulator, In the above-mentioned step, when the total mass (g) of (A), (B), and (C) is a, the number of moles of (D) is b, and the total number of moles of water and methanol contained in (A), (B), and (C) is c and d, respectively, the values are set so as to satisfy (b+c+d) / a=1.5 to 7 μmol / g.
[0010] (2) The method for producing a polyacetal copolymer according to (1) above, wherein the linear formal compound (D) is at least one selected from the group consisting of methylal, ethylal, and dibutoxymethane.
[0011] (3) The method for producing a polyacetal copolymer according to (1) or (2) above, wherein the aliphatic glycidyl ether compound (C) is an aliphatic glycidyl ether compound having one glycidyloxy group in one molecule.
[0012] (4) The method for producing a polyacetal copolymer according to (1) or (2) above, wherein the aliphatic glycidyl ether compound (C) is at least one selected from the group consisting of n-butyl glycidyl ether and 2-ethylhexyl glycidyl ether.
[0013] (5) A polyacetal copolymer obtained by the method for producing a polyacetal copolymer according to any one of (1) to (4) above. Effect of the Invention
[0014] According to the present invention, it is possible to provide a polyacetal copolymer having excellent rigidity, creep resistance and thermal stability, and a stable production method thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] <Production method of polyacetal copolymer> The method for producing the polyacetal copolymer of this embodiment includes a step of copolymerizing 100 parts by mass of trioxane (A), 0.05-5 parts by mass of a cyclic acetal compound (B), and 0.001-1 part by mass of an aliphatic glycidyl ether compound (C) having a chlorine content of 1-500 ppm by mass in the presence of a linear formal compound (D) as a molecular weight regulator. In this step, the total mass (g) of (A), (B), and (C) is a, the number of moles of (D) is b, and the total number of moles of water and methanol contained in (A), (B), and (C) is c and d, respectively, so that (b+c+d) / a=1.5-7 μmol / g is satisfied. First, each component used in the production method of this embodiment will be described below.
[0016] [Trioxane (A)] Trioxane (A) is a cyclic trimer of formaldehyde, and is generally obtained by reacting an aqueous formaldehyde solution in the presence of an acid catalyst, and is used after being purified by a method such as distillation. It is preferable that the trioxane (A) used for polymerization has impurities such as water and methanol reduced as much as possible.
[0017] [Cyclic acetal compound (B)] The cyclic acetal compound (B) is a cyclic acetal compound (B) copolymerizable with trioxane (A), and examples thereof include 1,3-dioxolane, propylene glycol formal, diethylene glycol formal, triethylene glycol formal, 1,4-butanediol formal, 1,5-pentanediol formal, and 1,6-hexanediol formal, with 1,3-dioxolane being preferred.
[0018] The copolymerization amount of the cyclic acetal compound (B) is 0.05 to 5 parts by mass, preferably 0.1 to 3 parts by mass, and more preferably 0.3 to 2.5 parts by mass, based on 100 parts by mass of the trioxane (A). If the copolymerization ratio of the cyclic acetal compound (B) is less than 0.05 parts by mass, the polymerization reaction becomes unstable and the thermal stability of the resulting polyacetal copolymer becomes poor. On the other hand, if the copolymerization ratio of the cyclic acetal compound (B) exceeds 5 parts by mass, mechanical properties such as strength and rigidity decrease.
[0019] [Aliphatic glycidyl ether compounds (C)] The aliphatic glycidyl ether compound (C) is a general term for an aliphatic organic compound having one or more glycidyloxy groups in the molecule, and has a structure that can form a branched or crosslinked structure in the polymer skeleton by copolymerization with trioxane. In this respect, it is distinguished from the cyclic acetal compound (B). As such an aliphatic glycidyl ether compound (C), either a monofunctional glycidyl ether compound having one glycidyloxy group or a polyfunctional glycidyl ether compound having two or more glycidyloxy groups can be used. A monofunctional glycidyl ether compound having one or more glycidyloxy groups is preferable.
[0020] Specific examples of the monofunctional glycidyl compound include methyl glycidyl ether, ethyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, 2-methyloctyl glycidyl ether, etc. Preferred are butyl glycidyl ether and 2-ethylhexyl glycidyl ether.
[0021] As the polyfunctional glycidyl compound having two or more glycidyloxy groups, a diglycidyl ether compound, a triglycidyl ether compound, and a tetraglycidyl ether compound are preferred.Specific examples of the polyfunctional glycidyl compound having two or more glycidyloxy groups include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, hexamethylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.
[0022] The copolymerization amount of the aliphatic glycidyl ether compound (C) is 0.001 to 1 part by mass, preferably 0.01 to 1 part by mass, and particularly preferably 0.1 to 1 part by mass, relative to 100 parts by mass of trioxane (A). If the copolymerization amount of the (C) component is less than 0.001 part by mass, the effect of improving rigidity and creep resistance cannot be obtained. On the other hand, if it exceeds 1 part by mass, problems such as poor moldability due to reduced fluidity may occur, and further, mechanical properties such as rigidity and creep resistance may be reduced due to reduced crystallinity of the obtained copolymer.
[0023] In this embodiment, from the viewpoint of rigidity and creep resistance, it is particularly preferable to use one or more compounds selected from n-butyl glycidyl ether and 2-ethylhexyl glycidyl ether as the aliphatic glycidyl ether compound (C).
[0024] The molecular weight of the aliphatic glycidyl ether compound (C) is preferably 100 to 220. If the molecular weight of the aliphatic glycidyl ether compound (C) exceeds 220, the branched chain of the polyacetal copolymer produced by its copolymerization becomes long, which may disturb the crystallinity of the resin, impair its basic properties, and may have an unfavorable effect on the rigidity and creep resistance. On the other hand, if the molecular weight of the (C) component is less than 100, the effect on the rigidity and creep resistance is extremely small.
[0025] In this embodiment, the aliphatic glycidyl ether compound (C) is characterized by having a chlorine content of 1 to 500 ppm by mass, which makes it possible to stably produce a polyacetal copolymer having particularly excellent thermal stability. The chlorine content is preferably 100 ppm by mass or less. With regard to the lower limit of the chlorine content, from the viewpoint of economic efficiency in the production of the aliphatic glycidyl ether compound (C), the chlorine content is preferably 1 ppm by mass or more. Furthermore, if the chlorine content of the aliphatic glycidyl ether compound (C) used exceeds 500 ppm by mass, operations such as the polymerization step, the terminal stabilization step, and the productization step by blending a stabilizer, etc., become unstable, and the thermal stability of the obtained polyacetal copolymer also becomes poor.
[0026] Aliphatic glycidyl ether compounds are generally produced by the reaction of alcohol with epichlorohydrin. Conventionally, a method (e.g., JP-A-61-178974) has been known in which epichlorohydrin is added to alcohol in the presence of an acid catalyst to open the ring, and then an aqueous alkali solution is used to close the ring in the molecule to obtain a glycidyl ether compound, but this production method is known to have a high chlorine content in the glycidyl ether compound. On the other hand, a method (e.g., JP-A-1-151567) has also been disclosed in which alcohol and epichlorohydrin are reacted in the presence of a solid alkali metal compound to produce a glycidyl ether compound, and the reaction is carried out in the presence of a solid alkali metal hydroxide pulverized in the reaction mixture. This production method has been shown to have an extremely low chlorine content in the glycidyl ether compound. In the present embodiment, for example, a glycidyl ether compound with an extremely low chlorine content obtained by such a method is used.
[0027] In this embodiment, the polyacetal copolymer is basically obtained by a method such as bulk polymerization of trioxane (A), a cyclic acetal compound (B), and an aliphatic glycidyl ether compound (C) with the addition of an appropriate amount of a molecular weight regulator as necessary, using a cationic polymerization catalyst.
[0028] In this embodiment, in order to obtain a polyacetal copolymer having better thermal stability, rigidity, impact resistance, etc., it is preferable that the structural units derived from the cyclic acetal compound (B) and the aliphatic glycidyl ether compound (C) are uniformly dispersed in the molecular chain of the polyacetal copolymer. For this purpose, when producing a polyacetal copolymer by polymerization, it is effective to uniformly mix the cyclic acetal compound (B) and the catalyst, add this to a homogeneous mixture of the aliphatic glycidyl ether compound (C) and trioxane (A) that have been homogeneously mixed separately in advance, and supply it to a polymerization machine to polymerize. By mixing them in advance to make a homogeneous solution state, the dispersion state of the branched structure derived from the aliphatic glycidyl ether compound becomes good, and not only the mechanical properties are improved, but also the thermal stability is excellent.
[0029] In producing the polyacetal copolymer of the present embodiment composed of the above-mentioned components, the polymerization apparatus is not particularly limited, and a known apparatus is used, and any method such as a batch method or a continuous method is possible. The polymerization temperature is preferably kept at 65 to 135° C. The deactivation after polymerization is performed by adding a basic compound or an aqueous solution thereof to the reaction product discharged from the polymerization machine after the polymerization reaction or to the reaction product in the polymerization machine.
[0030] Examples of the cationic polymerization catalyst used in this embodiment include lead tetrachloride, tin tetrachloride, titanium tetrachloride, aluminum trichloride, zinc chloride, vanadium trichloride, antimony trichloride, phosphorus pentafluoride, antimony pentafluoride, boron trifluoride, boron trifluoride diethyl etherate, boron trifluoride dibutyl etherate, boron trifluoride dioxanate, boron trifluoride acetic anhydrate, boron trifluoride triethylamine complex compounds, and other boron trifluoride coordination compounds, perchloric acid, acetyl perchlorate ... Examples of the catalyst include inorganic and organic acids such as triethyloxonium tetrafluoroborate, triphenylmethylhexafluoroantimonate, allyldiazonium hexafluorophosphate, and allyldiazonium tetrafluoroborate; alkyl metal salts such as diethylzinc, triethylaluminum, and diethylaluminum chloride; heteropolyacids; and isopolyacids. Among these, boron trifluoride, boron trifluoride diethyl etherate, boron trifluoride dibutyl etherate, boron trifluoride dioxanate, boron trifluoride acetic anhydrate, and boron trifluoride triethylamine complex compounds are particularly preferred. These catalysts can also be used by diluting them in advance with an organic solvent or the like.
[0031] The molecular weight regulator used in this embodiment is a linear formal compound. Examples of the linear formal compound include methylal, ethylal, dibutoxymethane, bis(methoxymethyl)ether, bis(ethoxymethyl)ether, and bis(butoxymethyl)ether. Among them, it is preferable to use one or more selected from the group consisting of methylal, ethylal, and dibutoxymethane.
[0032] As the basic compound for neutralizing and deactivating the polymerization catalyst, ammonia, amines such as triethylamine, tributylamine, triethanolamine, tributanolamine, or hydroxide salts of alkali metals or alkaline earth metals, or other known catalyst deactivators are used. After the polymerization reaction, it is preferable to quickly add an aqueous solution of such a compound to the product to deactivate it. After the polymerization method and deactivation method, washing, separation and recovery of unreacted monomers, drying, etc. are further carried out by a conventionally known method, if necessary.
[0033] Furthermore, stabilization treatment is performed by a known method as necessary, such as decomposition and removal of unstable terminals or blocking of unstable terminals with a stabilizing substance, and various necessary stabilizers are blended. The stabilizers used here can include one or more of hindered phenol compounds, nitrogen-containing compounds, hydroxides of alkali or alkaline earth metals, inorganic salts, carboxylates, etc. Furthermore, as long as they do not impair the effects of the polyacetal copolymer of this embodiment, one or more of general additives for polyacetal resins, such as colorants such as dyes and pigments, lubricants, nucleating agents, release agents, antistatic agents, surfactants, or organic polymer materials, inorganic or organic fibrous, powdery, or plate-like fillers, etc., can be added as necessary.
[0034] In this embodiment, in the copolymerization step, the total mass (g) of trioxane (A), cyclic acetal compound (B), and aliphatic glycidyl ether compound (C) is a, the number of moles of linear formal compound (D) is b, and the total number of moles of water and methanol contained in components (A), (B), and (C) is c and d, respectively, and the copolymerization step is set so as to satisfy (b+c+d) / a=1.5 to 7 μmol / g. When (b+c+d) / a=1.5 to 7 μmol / g is satisfied, the melt flow rate (MFR) measured according to ISO 1133 can be set to 0.5 to 3 g / 10 min. When the MFR is 0.5 to 3 g / 10 min, creep resistance can be improved while maintaining moldability. The MFR is particularly preferably 1 to 2.5 g / 10 min. The water and methanol contained in (A), (B) and (C) are derived from the respective impurities.
[0035] <Polyacetal copolymer> The polyacetal copolymer of the present embodiment is obtained by the above-mentioned method for producing the polyacetal copolymer of the present embodiment, and therefore has excellent rigidity, creep resistance, and the like, and also has thermal stability. EXAMPLES
[0036] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to the following examples.
[0037] [Examples 1 to 5] A continuous mixer reactor consisting of a barrel with a cross section of two overlapping circles with a jacket for passing a heat (cool) medium on the outside and a rotating shaft with paddles was used, and while rotating the two rotating shafts with paddles at 150 rpm, trioxane (A), a cyclic acetal compound (B), and an aliphatic glycidyl ether compound (C) were added in the ratios and amounts shown in Table 1. Furthermore, a linear formal compound (D) shown in Table 1 as a molecular weight regulator was continuously fed in the ratios and amounts shown in Table 1, and a homogeneous mixture of boron trifluoride gas as a catalyst was continuously added and fed to trioxane so that the boron trifluoride content was 0.005 mass% in terms of boron trifluoride, to perform bulk polymerization. The reaction product discharged from the polymerization reactor was quickly passed through a crusher and added to an aqueous solution containing 0.1 mass% triethylamine at 80°C to deactivate the catalyst. After separation, washing, and drying, a crude polyacetal copolymer was obtained.
[0038] Next, 4 parts by mass of a 5% by mass aqueous solution of triethylamine and 0.03 parts by mass of pentaerythrityl-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] were added to 100 parts by mass of this crude polyacetal copolymer, and the mixture was melt-kneaded at 210°C in a twin-screw extruder to remove unstable portions.
[0039] To 100 parts by mass of the branched or crosslinked polyacetal copolymer obtained by the above method, 0.3 parts by mass of pentaerythrityl-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 0.15 parts by mass of melamine were further added as stabilizers, and the mixture was melt-kneaded at 210°C in a twin-screw extruder to obtain a branched polyacetal copolymer in the form of pellets. The results of evaluation by the methods described below are shown in Table 2.
[0040] [Comparative Examples 1 to 5] As shown in Table 1, in cases where the chlorine content of the aliphatic glycidyl ether compound (C) is outside the range specified in this embodiment, and in cases where the MFR of the branched polyacetal copolymer is outside the range specified in this embodiment, etc., pellet-shaped polyacetal copolymers were obtained in the same manner as in the examples, and the evaluation results are shown in Table 2.
[0041] The abbreviations for each component listed in Table 1 have the following meanings. [Cyclic acetal compounds] DO; 1,3-dioxolane [Aliphatic glycidyl ether compounds] BGE; Butyl glycidyl ether 2EHGE; 2-Ethylhexyl glycidyl ether BDGE; Butanediol diglycidyl ether For each aliphatic glycidyl ether compound, a plurality of types having different chlorine contents were obtained by varying the synthesis method.
[0042] [Chlorine content] The chlorine content of the aliphatic glycidyl ether compound was measured by the following method. 50 mg of the measurement sample (5 mg for samples with a chlorine content of over 1000 ppm) was combusted and decomposed in a sample combustion device (AFQ-100, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) while introducing steam, and the generated gas was absorbed in an absorption solution with phosphate ions as the internal standard. This absorption solution sample was measured using an anion chromatograph (ICS-1600, manufactured by Dionex Co., Ltd.) to quantify the amount of chlorine ions and determine the chlorine content of the measurement sample.
[0043] [Total amount of water in components (A), (B), and (C)] The water content of the mixed liquid of components (A), (B), and (C) was measured by the Karl Fischer method.
[0044] [Total amount of methanol in components (A), (B), and (C)] A mixed liquid of components (A), (B), and (C) was used for the measurement by gas chromatography.
[0045] [MFR] The melt flow rate (MFR) of the polyacetal copolymer was measured according to ISO 1133.
[0046] <Evaluation> The flexural modulus, creep resistance and amount of formaldehyde generated of the polyacetal copolymer pellets according to the Examples and Comparative Examples were evaluated as follows. [Rigidity (flexural modulus)] The flexural modulus (FM) was measured in accordance with ISO 178. The conditions in the measurement room were 23°C and 55% RH. [Creep resistance properties (time to creep rupture)] ISO Type-A test pieces with a thickness of 4 mm were molded and creep tests were carried out using a creep tester under a load of 21 MPa in an 80°C environment, and the time to rupture (creep rupture time (h)) was compared. Three pieces were measured, and the average value was taken as the creep rupture time. [Thermal stability (amount of formaldehyde generated from the melt)] 5 g of the pellets were weighed accurately and kept in a metal container at 200°C for 5 minutes, after which the atmosphere in the container was absorbed into distilled water. The amount of formaldehyde in this aqueous solution was quantified according to JIS K0102, 29. (formaldehyde section) and the amount of formaldehyde gas (ppm) generated from the pellets was calculated.
[0047] [Table 1]
[0048] [Table 2]
[0049] Table 2 shows that Examples 1 to 9 can provide polyacetal copolymers having sufficient rigidity (flexural modulus of 2350 MPa or more) and excellent creep resistance (time to break of 500 hours or more) and thermal stability (low formaldehyde generation amount (150 ppm or less)). In contrast, Comparative Examples 1 to 5 had sufficient rigidity but were inferior in at least one of creep resistance and thermal stability. In particular, Examples 1 to 7 and Comparative Examples 1 and 2, Example 8 and Comparative Example 3, and Example 9 and Comparative Example 4 have different chlorine contents in the aliphatic glycidyl ether compound, and a comparison between them shows that the thermal stability is inferior when the chlorine content is not within a specified range. Furthermore, from each of the Examples and Comparative Examples in Table 1, it can be seen that the MFR of the polyacetal copolymer can be set to 0.5 to 3 g / 10 min by setting the ratio of the specific components to (b+c+d) / a = 1.5 to 7 μmol / g.
Claims
1. The method includes a step of copolymerizing 100 parts by mass of trioxane (A), 0.05 to 5 parts by mass of a cyclic acetal compound (B), and 0.001 to 1 part by mass of an aliphatic glycidyl ether compound (C) having a chlorine content of 40 to 320 ppm by mass in the presence of a linear formal compound (D) as a molecular weight regulator, In the above-mentioned step, when the total mass (g) of (A), (B), and (C) is a, the number of moles of (D) is b, and the total number of moles of water and methanol contained in (A), (B), and (C) is c and d, respectively, the values are set so as to satisfy (b+c+d) / a=1.5 to 7 μmol / g.
2. 2. The method for producing a polyacetal copolymer according to claim 1, wherein the linear formal compound (D) is at least one selected from the group consisting of methylal, ethylal, and dibutoxymethane.
3. 3. The method for producing a polyacetal copolymer according to claim 1, wherein the aliphatic glycidyl ether compound (C) is an aliphatic glycidyl ether compound having one glycidyloxy group in one molecule.
4. 3. The method for producing a polyacetal copolymer according to claim 1, wherein the aliphatic glycidyl ether compound (C) is at least one selected from the group consisting of n-butyl glycidyl ether and 2-ethylhexyl glycidyl ether.
Citation Information
Patent Citations
Polyacetal copolymer
JP2000038429A
Polyacetal copolymer
JP2000095829A
Polyacetal copolymer
JP2000095830A
Polyacetal copolymer and its production
JP2000264940A
Polyacetal copolymer and its preparation method
JP2002234922A